2016
DOI: 10.1002/bdm.1975
|View full text |Cite
|
Sign up to set email alerts
|

Social Value Orientation Moderates the Effects of Intuition versus Reflection on Responses to Unfair Ultimatum Offers

Abstract: We investigated whether social value orientation (SVO) moderates the effects of intuitive versus reflective information processing on responses to unfair offers. We measured SVO one week prior to an ultimatum game experiment in which participants had to accept or reject a series of 10 ultimatum offers including very low (unfair) ones. Before making these decisions, participants mentally contrasted their individual goals with the obstacle of pondering at length or acting in a hasty way; then they made the plan … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 92 publications
(123 reference statements)
3
40
0
Order By: Relevance
“…For instance, if one nurse is suffering from emotion control problems whereas another is overly impulsive, knowing about this by handing out relevant personality questionnaires at the outset of the study would allow gearing their wishes to more effectively cope with these shortcomings. Recent research shows that MCII can indeed be targeted toward affective aspects of one’s outcome and obstacle ( Ruissen et al, 2018 ) or toward enhancing reflection over impulsivity ( Bieleke et al, 2017 ).…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, if one nurse is suffering from emotion control problems whereas another is overly impulsive, knowing about this by handing out relevant personality questionnaires at the outset of the study would allow gearing their wishes to more effectively cope with these shortcomings. Recent research shows that MCII can indeed be targeted toward affective aspects of one’s outcome and obstacle ( Ruissen et al, 2018 ) or toward enhancing reflection over impulsivity ( Bieleke et al, 2017 ).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Implementation intentions’ self-regulatory benefits for action control extend into emotion regulation as well (e.g., fear, disgust, and anger; summary by Webb et al, 2012 ). Finally, with respect to the regulation of cognitive responses research demonstrated that if-then plans help people to switch from reflexive to reflective thinking thus improving decision making (e.g., Bieleke et al, 2017 ).…”
Section: Self-regulation By Implementation Intentions (Ii)mentioning
confidence: 99%
“…The integrative model of SVO assumes that the prosocials differ from the proselfs in two aspects: the weight assigned to other's outcomes and the weight assigned to the equality of outcomes ( Van Lange, 1999 , 2000 ). Thus, this model implies that relative to proselfs, the prosocials’ evaluation of outcomes are influenced by considerations of others’ outcomes and fairness, and the prosocials tend to pay more attention to outcomes for others ( De Cremer and Van Lange, 2001 ; Bieleke et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A relevant factor affecting people reactions to another player’s choice when playing an economic game is prosociality, which can be defined as the concern people have for others (Bieleke et al, 2016 ; for prosocial behavior in economic games, see also Camerer, 2003 ). In order to control for the impact of this dimension, after the attention task we measured a trait of prosociality in the participants using the SVO Slider Measure (Murphy et al, 2011 ) .…”
Section: Methodsmentioning
confidence: 99%